Trehalose Ameliorates Diabetic Cardiomyopathy: Role of the PK2/PKR Pathway. (21st December 2021) - Liu, Yuning; Wu, Shi; Zhao, Qian; Yang, Zhen; Yan, Xiaojun; Li, Cairong; Zha, Wenliang; Yu, Wei
Abstract : Ample clinical case reports suggest a high incidence of cardiomyopathy in diabetes mellitus (DM). Recent evidence supports an essential role of trehalose (TLS) in cardiomyocyte survival signaling. Our previous study found that prokineticin2 (PK2) was involved in the process of diabetic cardiomyopathy (DCM). The present study examined the protective effects and mechanisms of TLS on DM-induced cardiomyocyte injury in mice and H9c2 cardiomyocytes. C57BL/6J mice were intraperitoneally injected with 50 mg·kg -1 ·d -1 streptozotocin for five consecutive days to establish an experimental diabetic model and then administered TLS (1 mg·g -1 ·d -1, i.p.) for two days every 4 weeks and given 2% TLS in drinking water for 24 weeks. Echocardiography, myocardial structure, apoptosis, pyroptosis, autophagy, and the PK2/PKR pathway were assessed. Cardiomyocytes exposed to high glucose (HG) were treated with TLS in the absence or presence of the PK2 antagonist PKRA7, and proteins involved in apoptosis, autophagy, and pyroptosis and the PK2/PKR pathways were evaluated using Western blot analysis. Diabetic mice demonstrated metabolic disorder, abnormal myocardial zymograms, and aberrant myocardial systolic and diastolic function, which were accompanied by pronounced apoptosis, pyroptosis, and dampened autophagy. TLS treatment relieved these effects. PK2 and receptor expressions were downregulated in diabetic mice, and TLS nullified this effect. PKRA7 eliminated the impact of TLS on cardiomyocytes. This evidence suggests that TLS rescues DM-induced myocardial function, pyroptosis, and apoptosis, likely via the PK2/PKR pathway.